2022
DOI: 10.1186/s13023-022-02542-z
|View full text |Cite
|
Sign up to set email alerts
|

Whole exome sequencing in Brugada and long QT syndromes revealed novel rare and potential pathogenic mutations related to the dysfunction of the cardiac sodium channel

Abstract: Background Brugada syndrome (Brs) and long QT syndrome (LQTs) are the most observed “inherited primary arrhythmia syndromes” and “channelopathies”, which lead to sudden cardiac death. Methods Detailed clinical information of Brs and LQTs patients was collected. Genomic DNA samples of peripheral blood were conducted for whole-exome sequencing on the Illumina HiSeq 2000 platform. Then, we performed bioinformatics analysis for 200 genes susceptible to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…In particular, a decrease in current density, a positive shift in the activation curve, a negative shift in the inactivation curve, or a loss of regulation by intracellular factors such as PKA, ankyrin G or a1-syntrophin have been described [22,29,[37][38][39][40][41] (Figure 2). Consistently, cardiomyocytes derived from mice models or patients' stem cells displayed a reduction in INa density and a reduction in AP upstroke velocity and altered ECG parameters [42].…”
Section: Scn5a Variants: Genotype-phenotype Correlationmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, a decrease in current density, a positive shift in the activation curve, a negative shift in the inactivation curve, or a loss of regulation by intracellular factors such as PKA, ankyrin G or a1-syntrophin have been described [22,29,[37][38][39][40][41] (Figure 2). Consistently, cardiomyocytes derived from mice models or patients' stem cells displayed a reduction in INa density and a reduction in AP upstroke velocity and altered ECG parameters [42].…”
Section: Scn5a Variants: Genotype-phenotype Correlationmentioning
confidence: 99%
“…The variants can either impair membrane trafficking or modify channel gating properties or kinetics or cause haploinsufficiency determined by premature transcriptional stop signals. In particular, a decrease in current density, a positive shift in the activation curve, a negative shift in the inactivation curve, or a loss of regulation by intracellular factors such as PKA, ankyrin G or a1-syntrophin have been described [ 22 , 29 , 37 , 38 , 39 , 40 , 41 ] ( Figure 2 ).…”
Section: Genetics and Molecular Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aforementioned variants may impair membrane trafficking, modify channel gating properties or kinetics, or cause haploinsufficiency due to premature transcriptional stop signals. Specifically, previous research has revealed a decrease in I Na and I K1 density and conduction www.cardiologyplus.org Huang K and Ren J: Cardiology Plus velocities or a loss of regulation by intracellular factors in signal transduction, including protein kinase A (PKA), ankyrin G, or a1-syntrophin [20][21] .…”
Section: Genetic Findings Of Brugada Syndromementioning
confidence: 99%